Tongue–lip adhesion and tongue repositioning for obstructive sleep apnoea in Pierre Robin sequence: A systematic review and meta-analysis. Issue 5 (14th February 2017) - Camacho, M; Noller, M W; Zaghi, S; Reckley, L K; Fernandez-Salvador, C; Ho, E; Dunn, B; Chan, D K
Abstract: Objective: To search for studies on tongue–lip adhesion and tongue repositioning used as isolated treatments for obstructive sleep apnoea in children with Pierre Robin sequence. Methods: A systematic literature search of PubMed/Medline and three additional databases, from inception through to 8 July 2016, was performed by two authors. Results: Seven studies with 90 patients (59 tongue–lip adhesion and 31 tongue repositioning patients) met the inclusion criteria. Tongue–lip adhesion reduced the mean (± standard deviation) apnoea/hypopnoea index from 30.8 ± 22.3 to 15.4 ± 18.9 events per hour (50 per cent reduction). The apnoea/hypopnoea index mean difference for tongue–lip adhesion was −15.28 events per hour (95 per cent confidence interval = −30.70 to 0.15; p = 0.05). Tongue–lip adhesion improved the lowest oxygen saturation from 75.8 ± 6.8 to 84.4 ± 7.3 per cent. Tongue repositioning reduced the apnoea/hypopnoea index from 46.5 to 17.4 events per hour (62.6 per cent reduction). Tongue repositioning improved the mean oxygen saturation from 90.8 ± 1.2 to 95.0 ± 0.5 per cent. Conclusion: Tongue–lip adhesion and tongue repositioning can improve apnoea/hypopnoea index and oxygenation parameters in children with Pierre Robin sequence and obstructive sleep apnoea.